CHARACTER EDUCATION IN ISLAMIC EDUCATION LEARNING: AN ANALYSIS OF CHARACTER VALUES IN ISLAMIC EDUCATION TEXTBOOK FOR MADRASAH TSANAWIYAH - Dini Apriliani Khairunissa Gurnadi (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the character education values embedded in Islamic Religious Education (PAI) textbooks used at the Madrasah Tsanawiyah level, focusing on how these values are represented across different subject areas. This research employs a qualitative approach with a library research design. The primary method used is content analysis to systematically examine the textual content of officially published PAI textbooks by the Ministry of Religious Affairs of the Republic of Indonesia. The analysis covers four subjects: Al-Qur’an Hadith, Aqidah Akhlak, Fiqh, and Islamic Cultural History (SKI), particularly for Grade 8. The findings reveal that the textbooks incorporate five core character values promoted in the Strengthening Character Education (PPK) program: religious, nationalist, independent, mutual cooperation, and integrity. Among these, religious values are the most dominant and consistently emphasized across all subjects, particularly in relation to faith, worship, and moral behavior. However, other values such as nationalism and independence are not evenly distributed and tend to receive less emphasis in certain subjects. This study is limited to the analysis of Grade 8 PAI textbooks and does not include empirical validation through classroom implementation or student outcomes. Nevertheless, the findings provide important implications for curriculum developers and educators to ensure a more balanced integration of character values across all subjects in Islamic education. This study offers originality by specifically examining the integration of character education values across multiple PAI subject areas within Madrasah Tsanawiyah textbooks, which has not been extensively explored in previous research. It contributes to the development of more systematic and comprehensive character education in Islamic educational contexts.